THE OPTIMIZATION OFPUJI-PUJIAN TRADITION BEFORE PRAYING IN CONGREGATION IN MOSQUES AND MUSHALLA AS A MEDIUM OF DA’WAH AND PREVENTION OF CORRUPTION - Aris Fauzin (Asia Pacific Fraud Journal, 2018)
The tradition of puji-pujian (praise) before praying in congregation conducted by the Muslim community in Indonesia is a unique tradition that is not carried out by Muslim communities abroad. This tradition has been going on since the Walisongo era until now. In its development, the tradition has undergone many changes. Lately, this puji-pujian (praise) tradition that was recited in many regional language poems has been replaced by modern sholawat. In fact, the praise tradition was initially a medium of da’wah to invite, to advise, and to teach religious values to the public. This means that its function becomes reduced. Associated with the existence of a large enemy, called corruption, which has damaged the order of life of the nation and state, the author tries to analyze the possibility to optimize the praise tradition before praying in congregation as a medium of da’wah and prevention of corruption. In this study, the author uses direct observation method to the practice of the implementation of the Muslim praise traditions in the areas of Cilacap, Central Java, and Sukabumi-Cianjur, West Java.